On the synthesis of quinone-based BODIPY hybrids: New insights on antitumor activity and mechanism of action in cancer cells. Issue 18 (15th September 2017) - Gontijo, Talita B.; de Freitas, Rossimiriam P.; Emery, Flavio S.; Pedrosa, Leandro F.; Vieira Neto, José B.; Cavalcanti, Bruno C.; Pessoa, Claudia; King, Aaron; de Moliner, Fabio; Vendrell, Marc; da Silva Júnior, Eufrânio N.
Graphical abstract: Abstract: Fluorescent quinone-based BODIPY hybrids were synthesised and characterised by NMR analysis and mass spectrometry. We measured their cytotoxic activity against cancer and normal cell lines, performed mechanistic studies by lipid peroxidation and determination of reduced (GSH) and oxidized (GSSG) glutathione, and imaged their subcellular localisation by confocal microscopy. Cell imaging experiments indicated that nor-β-lapachone-based BODIPY derivatives might preferentially localise in the lysosomes of cancer cells. These results assert the potential of hybrid quinone-BODIPY derivatives as promising prototypes in the search of new potent lapachone antitumor drugs.